Creation and verification of an RP-UHPLC technique for abemaciclib and associated impurities in formulations and APIs using Box-Behnken design - Kalpana Krishnaraju; Malarkodi Velraj (Creative Pharma Assent, 2026)
Background: Strict impurity profiling is necessary to ensure the safety, effectiveness, and regulatory compliance of Abemaciclib (AbB), a selective CDK4/6 inhibitor frequently used in breast cancer treatment. However, a lack of thorough impurity separation, lengthy run times, and low sensitivity are common problems with current analytical techniques. Methodology: A novel reverse-phase ultra-high-performance liquid chromatography (RP-UHPLC) method was developed using a Quality by Design (QbD) framework. Critical method parameters, including mobile phase pH, flow rate, and column temperature, were optimized using Box-Behnken Design (BBD). Chromatographic separation was achieved on a C18 column using an isocratic mobile phase consisting of acetonitrile (40:60, v/v) and ammonium formate buffer (pH 2.7). The technique was validated in accordance with the ICH Q2(R1) requirements. Results and Discussion: The optimized method demonstrated exceptional linearity over the range of 0.02–150 μg/mL (R² > 0.999) with excellent precision (RSD < 2% for AbB and < 10% for related impurities) and showed acceptable accuracy, with mean recoveries ranging from 92.76% to 102.88% across AbB and its related impurities. The detection and quantification limits for AbB were 0.01 μg/mL and 0.02 μg/mL, respectively. Forced degradation studies that effectively distinguished degradation products in oxidative, acidic, and alkaline settings confirmed the method's stability-indicating nature. The 8-minute run time allowed for quick examination. The integration of BBD-based QbD significantly enhanced method robustness, resolution, and sensitivity compared to conventional chromatographic approaches, allowing simultaneous quantification of AbB and its related impurities. Conclusion: For routine quality control, stability investigations, and regulatory-compliant impurity profiling of Abemaciclib, the developed RP-UHPLC method is quick, sensitive, reliable, and appropriate.